Evaluation of Fairness of Trademarks Royalty Prices in Transfer Pricing Transactions (Case Study of PT X Court Decisions) - Intan Puspanita; Danny Septriadi (CIC Lembaga Riset dan Konsultan Sosial, 2021)
ABSTRACT This study aims to analyze the arm’s length price of transfer pricing transactions for parties conducting cross-border transactions as well as to see the basis and considerations of the panel of judges regarding royalty on trademark license for tax court decision disputes. The method used in this research is a qualitative approach by looking at the sources of books, documents, national and international journals, as well as laws related to the research topic of transfer pricing. The results of this study concluded that the beneficial owner of IP was Friesland Brands BV, therefore the economic ownership of the IP was Friesland Brands BV because it had developed and continued to develop royalties on the trademark of data, methods, processes, capabilities, and expertise in connection with the milk-making activity. The Panel of Judges did not use the various meanings of a trademark to prove the existence of the trademark. The definition of a trademark that can be used by judges to prove the existence of a trademark is based on international and domestic provisions. Keywords: arm’s length price, tax dispute, trademarks ABSTRAK Penelitian ini bertujuan untuk menganalisis harga wajar atas transaksi transfer pricing bagi pihak-pihak yang melakukan transaksi lintas negara serta melihat dasar dan pertimbangan majelis hakim terkait royalty on trademark lisence atas sengketa putusan pengadilan pajak. Metode yang digunakan dalam penelitian ini yaitu menggunakan pendekatan kualitatif dengan melihat berbagai sumber antara lain yaitu buku-buku, dokumen, jurnal nasional dan internasional, serta undang-undang yang terkait dengan topik transfer pricing. Hasil penelitian ini memperoleh kesimpulan bahwa beneficial owner atas IP adalah Friesland Brands BV, oleh karena itu economic ownership atas IP tersebut adalah Friesland Brands BV karena telah mengembangkan dan melanjutkan untuk mengembangkan royalty on trademark tersebut atas data, metode, proses, kemampuan dan keahlian sehubungan dengan aktivitas pembuatan susu tersebut. Majelis Hakim tidak menggunakan berbagai pengertian merek dagang untuk melakukan pembuktian keberadaan merek dagang tersebut. Pengertian merek dagang yang dapat digunakan hakim untuk membuktikan keberadaan trademark (merek dagang) tersebut berdasarkan ketentuan internasional dan domestik. Kata Kunci: harga wajar, sengketa pajak, trademarks